Persyaratan Umum Tentang Kemasan - Wiwik Pudjiastuti (Jurnal Kimia dan Kemasan, 2001)
Export packaging must meet the global market requirements which is, at present, mainly influenced by the consumer awareness in safety and environmental protection, and modern logistic distribution. General requirements needed to be considered in the export packagingdevelopment are as follws : Requirement for safety use, llALAL food symbol, dangerous goods packaging, requirement for requirement for environmental protetion and requirement for packaging size standardization.